The impact of human capital efficiency on Latin American mutual funds during Covid-19 outbreak - Nawazish Mirza; Jamila Abaidi Hasnaoui; Bushra Naqvi; Kumail Abbas Rizvi (Swiss Journal of Economics and Statistics, 2020)
The mutual funds' returns, inter alia, are dependent on fund managers' performance. This makes human capital efficiency very central for consistent risk-adjusted performance. The persistence in performance becomes more critical during periods of high turbulence, like the one we are experiencing amidst the outbreak of Covid-19. In this research, we attempt to evaluate the performance of equity funds in massively impacted Latin American countries. These equity funds, with 95% of their investment in the infected region, are ranked as per their human capital efficiency using 2019 as the base year. Our findings demonstrate that funds with higher human capital efficiency significantly outperform their counterparts that rank lower on human capital efficiency. These findings remained consistent for the sub-periods that we specify to map the evolution of Covid-19. We conclude that equity funds should enhance their human capital efficiency to endure resilience amid macroeconomic shocks.
Keywords: G01; G10; G11; G20; 330; Covid-19; Equity funds; Latin America; Human capital; Investmentfonds; Fondsmanagement; Kapitalmarktrendite; Humankapital; Coronavirus; Lateinamerika